Overexpression of Lipase Gene from Alcaligenes sp. JG3 and its Activity toward Hydrolysis Reaction - Norman Yoshi Haryono; Winarto Haryadi; Tri Joko Raharjo (Universitas Gadjah Mada, 2020)
Bacterial lipase holds an important role as a new source for many industrial catalysts. The investigation and understanding of the lipase-encoding gene become apparent as the key step for generating high-quality lipase as biocatalyst for many chemical reactions. In this study, bacterial lipase from Alcaligenes sp. JG3 was produced via overexpression gene method. This specific lipase was successfully overexpressed using pQE-30 vector and E. coli M15[pREP4] as host, producing His-tagged protein sized 46 kDa and was able to hydrolyze triacylglycerol from olive oil with the calculated unit activity and specific activity of 0.012 U and 1.175 U/mg respectively. The in silico investigation towards lipase JG3 revealed that it was categorized as ABC transporter protein as opposed to the conventional hydrolase family. Lastly, amino acid sequences SGSGKTT from lipase JG3 was highly conserved sequences and was predicted as the ATP-binding site but the catalytic triad of serine, histidine, and aspartate has not been solved yet.